Evaluación de perfiles de huella hídrica: Análisis del ciclo de vida de la quinua en Bolivia - Javier Aliaga Lordemann; Alejandro Capriles; Nayra Antezana (Institute for Advanced Development Studies (INESAD), 2024)
– This study analyzes the water footprint profiles of quinoa production in Bolivia, an emblematic crop that faces significant challenges in terms of yield and sustainability. The Total Water Footprint (WH) of quinoa estimated for the Southern Altiplano region of Bolivia is approximately 1,728 liters per kilogram, with average yields of 1.15 tons per hectare. This result shows a worrying level of inefficiency in the relationship of HH and crop yield, especially in comparison with countries such as Peru and Ecuador. The results show high HH and low yields; therefore, quinoa production in Bolivia in the study area is not optimizing water use. This situation can be explained to a large extent by the low level of organic matter in the soil of the area (verified by soil studies). Thus, a soil with low organic matter content lacks essential nutrients, which impairs quinoa growth and negatively affects its root development due to soil compaction. In addition, the lack of organic matter decreases water retention capacity, which is critical in periods of drought as a result of the increased frequency and intensity of climatic events in the area. Likewise, the lack of organic matter makes plants more vulnerable to pests and diseases, but also reduces microbial biodiversity, which affects key processes such as decomposition and nutrient cycling, compromising soil fertility. In summary, this type of soil is less efficient in water use, which can increase the water footprint of the crop by requiring more frequent irrigation. Based on these conclusions, several recommendations are proposed. First, it is crucial to optimize yield and reduce WH by implementing efficient irrigation systems. This includes training farmers in these technologies. The use of vegetative covers that improve moisture retention is also suggested. In addition, advanced irrigation technologies -such as soil moisture sensors- should be adopted and rainwater harvesting systems should be promoted. Training in integrated water resources management is essential, as well as the development of climate adaptation strategies.
Keywords: Q57; Q56; Q15; Q25; C21; 330; Total Water Footprint (WH); life cycle; water productivity; econometric analysis; agricultural sustainability